The Influence of Income, Planning, Financial Literacy to Financial Management of Muslim MSMEs in Kudus Regency - Ahmad Nilnal Munachifdlil Ula; Faridhatun Faidah; Indah Puspita Maharani; Diah Ayu Susanti; Mohammad Khasan; Ridwan (CV. Sakura Digital Nusantara, 2026)
Purpose – This study aims to analyze the influence of income, financial planning, and financial literacy on the financial management of Muslim MSMEs in Kudus Regency. Design/Methodology/Approach – A quantitative approach was applied in this study by distributing questionnaires using purposive sampling to 96 Muslim MSMEs in Kudus. The collected primary data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3 software. The analysis included measurement model evaluation, structural model evaluation, bootstrapping, coefficient of determination, and model fit assessment. Findings/Results – The empirical results show that income (β = 0.439, p < 0.001) and financial planning (β = 0.386, p = 0.009) have positive and statistically significant effects on the financial management of Muslim MSMEs in Kudus. Conversely, financial literacy does not have a statistically significant effect (β = 0.119, p = 0.160), indicating that financial knowledge alone does not necessarily translate into effective financial management practices within this specific socio-religious context. The model demonstrates explanatory power (R² = 0.651) and highlights the roles of income and financial planning in shaping financial management behavior. These findings indicate that financial capacity and structured planning are more directly associated with financial management outcomes in this context. Originality/Value – This study extends the behavioral finance literature by contextualizing the findings within a specific religio-regional ecosystem. It uses the local cultural philosophy of